Prevalence of iron deficiency and iron deficiency anaemia among nursing students of Bilaspur Chhattisgarh - Saha, Jayanta; Sarkar, Derbashree (International Journal of Medical Research and Review, 2015)
Background and Aim: The most widespread nutritional problem is iron deficiency affecting over two billion people. It is particularly common disorder among infants, preschool children, young women and older people but it can occur at ages and in any region. A high demand for iron during rapid growth, pregnancy and lactation, accompanied by dietary deficiency in children and young women, can lead to iron deficiency anaemia. Materials and Methods: The present study carried out at Department of Biochemistry, Chhattisgarh Institute of Medical Sciences, Bilaspur (CG). A total 112 female students participated in this cross sectional study was age between 18-25 years. Complete blood cell count and Serum iron, Ferritin, total iron binding capacity were used to assess the status of iron deficiency and iron deficiency anaemia. Results: We found significant (P<0.001) decrease level of Serum Iron and Ferritin and significant (P<0.001) increased level of TIBC in ID as well as IDA as compared to Normal. In this study, the prevalence rates of ID and IDA in female university students aged 18–25 years were 55.35% and 10.7%, respectively. Conclusion: The results of this study indicate that iron supplementation is required for the target group. Finally, nutrition education and intervention program should address ID with a focus on both the dietary quantity and the quality of the micronutrient composition. All of these interventions must be monitored for effectiveness.